Influence of protein characteristics and the proportion of gluten on end-use quality in Korean wheat cultivars - Seong-Woo Cho; Chon-Sik Kang; Hyeon Seok Ko; Byung-Kee Baik; Kwang-Min Cho; Chul Soo Park (Journal of Integrative Agriculture, 2018)
The effects of protein characteristics and the proportion of gluten on end-use quality in 13 Korean wheat cultivars for three years were verified in this study. Year, cultivar, and the interaction between the year and the cultivar influenced protein characteristics, the proportion of gluten except for γ- and ω-gliadin using RP-HPLC (reversed-phase high-performance liquid chromatography), and end-use quality. Protein characteristics and the proportion of gluten in Korean wheat cultivars were between those of Australian standard white (ASW) and hard wheat (AH). Korean wheat cultivars exhibited a higher average α+β gliadin proportion than imported wheat, a γ-gliadin proportion similar to that of dark northern spring wheat, and the same ω-gliadin proportion as AH. They showed a bread-loaf volume intermediate between those of ASW and AH and a texture of cooked noodles similar to that of soft white wheat, but less springiness than imported wheat. The cookie diameter of Korean wheat cultivars was similar to that of hard red winter wheat. There was a correlation between bread-loaf volume and protein characteristics, except for the protein content in Korean wheat cultivars. Springiness and cohesiveness of cooked noodles were not correlated with protein characteristics, while hardness was correlated with the protein content and water absorption of a mixograph. Cookie diameter was negatively correlated with the sodium dodecyl sulfate (SDS) sedimentation volume and water absorption of a mixograph. The end-use quality was not correlated with any proportion of gluten composition. Principal component analysis (PCA) showed that the proportion of gluten was not related to the quality of the bread (both PCs, 81.3%), noodle (77.7%), and cookie (82.4%). PCA explained that Keumkang is suitable for superior bread, while Uri is good for cooked noodles and cookies.